Kadar Alkaloid, Makanan dan Daya Terima Lacto Cookies dengan Substitusi Tepung Jantung Pisang (Musa Paradisiaca Linn.) dan Tepung Ikan Seluang (Rasbora argyrotaenia): Alkaloid, Protein, Dietary Fiber Content, and Acceptability of Lacto Cookies Substituted with Banana Blossom (Musa Paradisiaca Linn.) and Fish Flour (Rasbora Argyrotaenia) - Nopriantini Nopriantini; Marudut Marudut; Syah R. Purba; Devi Novia; Edy Waliyo; Julianto Gambir (Universitas Airlangga, 2023)
Introduction: The smooth creation of bosom milk (ASI) given to infants can emphatically affect the wholesome status of children. Breast milk production can be smooth if the hormones oxytocin and prolactin increase. Banana heart (Musa paradisiaca) contains Laktagogum, which can stimulate hormones, Oxytocin, and Prolactin, such as alkaloids, polyphenols, steroids, and flavonoids. In seluang fish (Rasbora Argyrotaenia), there are nine essential amino acids (histidine, arginine, threonine, valine, methionine, isoleucine, and leucine. Objectives: This study analyzed the acceptability of five cookie formulations and alkaloids, protein, and fiber content. Methods: This study used a completely randomized AA design (CRD) D with N5 treatments. The research subjects were 25 people for the acceptability test. Alkaloids were carried out using the UV-is spectrophotometric method, proteins using the Kjeldahl method, and fiber using the enzymatic gravimetric method. Results: Regarding color, taste, and aroma, formula 2 (40% banana heart, 10% seluang fish) was significantly more acceptable with a mean p<0.001 (3.06±0.97). Formula 2 (40% banana heart, 10% seluang fish) in 100 grams contains 110.03 g/100 g alkaloids, 25.79% protein, and 21.06% crude fiber. Conclusions: The most preferred formula is formula 2, with alkaloid content of 110.03 g/100 g, protein of 25.79%, and crude fiber 21.0.